Virtual Laboratories: Mesocosms and Gameworlds - Dustin Breitling (Teorie vědy)
This article explores the role of digital games as virtual laboratories for addressing ecological and climate change challenges. It begins by examining the intersection of citizen science and digital gaming, specifically initiatives that have enabled global communities to contribute to ecosystem preservation efforts through collaborative data collection, analysis, and problem-solving that have been vital for monitoring marine habitats. Building upon these developments, we will explore how digital games share parallels with mesocosms, attempting to render ecological and Earth systems phenomena legible while simultaneously contributing to contemporary debates surrounding biodiversity, species loss, and climate change. Notably, digital gameworlds have expanded their scope beyond simple ecological simulations, incorporating intricate climate models alongside social, political, and historical elements to craft nuanced, evolving virtual environments that attempt to reflect the fragile interconnection of systems on a planetary scale.